Process for depolymerizing polyesters

By using a mixture of alkaline compounds and alcohol or ketone solvents to depolymerize polyester under mild conditions, the problem of low conversion rate is solved, enabling efficient polyester recycling and reducing chemical and equipment costs.

CN121002107APending Publication Date: 2025-11-21KIRIN HOLDINGS KK

Patent Information

Application Number
CN202480027957.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-28
Filing Date
2024-04-26
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing polyester depolymerization methods have low conversion rates under mild conditions and suffer from solvent degradation, which affects industrial recycling efficiency.

Method used

Polyester depolymerization is carried out at temperatures below 75°C using a mixture containing alkaline compounds such as sodium hydroxide and alcohols or ketones as solvents. The mass ratio of polyester to solvent is controlled within the range of 0.2 to 20, and the mixture contains polyester particles with a particle size of 150 to 350 μm.

Benefits of technology

It enables efficient conversion of polyester to terephthalate and ethylene glycol under mild conditions, improving recycling efficiency and reducing chemical costs and equipment complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a method for depolymerizing polyester. The method comprises forming a polyester comprising the following components (a), (b) and (c): (a) a polyester, (b) one or more basic compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonate salts, alkaline earth metal hydroxides, alkaline earth metal carbonates and alkaline earth metal bicarbonate salts, and (c) and a step of depolymerizing the polyester in the mixture of a solvent containing at least one of an alcohol-based solvent and a ketone-based solvent. The temperature of the mixture at the time when the mixture containing the total amount of the polyester, the basic compound, and the solvent is formed is 75 DEG C or less. The ratio of the amount of the polyester to the amount of the solvent is 0.2-20 by mass.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a method for depolymerizing a polyester. BACKGROUND

[0002] Recently, environmental pollution caused by plastic waste has become a problem. In order to reduce the environmental load, development of basic technologies for efficiently recycling plastic products has become a pressing matter. Among plastic products, polyesters are also used in large amounts as beverage bottles or fibers. Therefore, it is desirable to establish an efficient recycling method.

[0003] As a recycling method for used polyester products, material recycling and chemical recycling are known. Material recycling is a method in which a used polyester product is directly melted and reshaped in the state of a resin after sorting, but since impurities cannot be completely removed, it is difficult to restore the quality before recycling. On the other hand, chemical recycling is able to produce a product of the same quality as the original polyester product in principle by first chemically decomposing into a low molecular compound.

[0004] As a method of chemical recycling of polyesters, there are roughly hydrolysis method using water as a solvent, alcoholysis method using alcohol as a solvent, and glycerolysis method using glycol as a solvent. In addition to these three, in recent years, depolymerization using microorganisms has also been studied.

[0005] The hydrolysis method is a method in which a polyethylene terephthalate melt is reacted with water vapor, and then with ammonium hydroxide, thereby decomposing into terephthalic acid and ethylene glycol. This method has the advantage that it does not require the use of glycol or alcohol for the reaction, but in order to perform the above reaction under high pressure conditions, a special device that can withstand pressure is required.

[0006] The alcoholysis method is a method in which a polyester is depolymerized by heating in an alcohol solvent. In this method, for example, in the case of depolymerizing polyethylene terephthalate (PET) using methanol as a solvent, since dimethyl terephthalate is generated as a monomer by the depolymerization reaction, it has the advantage of being efficient and the depolymerization reaction is also relatively fast. However, the alcohol used as a solvent has a low boiling point, and in order to perform the reaction, it needs to be pressurized, so a special device that can withstand pressure is required.

[0007] The glycerolysis method is a method in which a polyester is depolymerized by heating in an excess of an alkylene glycol solvent with a depolymerization catalyst such as sodium carbonate, to produce bis(hydroxyalkyl) terephthalate and ethylene glycol. The glycerolysis method can be reacted under normal pressure, but has the problem of a long reaction time.

[0008] The method using microorganisms is a method of obtaining terephthalic acid by hydrolyzing polyethylene terephthalate using an enzyme, and although it can perform the hydrolysis reaction under mild reaction conditions, there is room for improvement in terms of efficiency.

[0009] In addition to these chemical recycling methods, as a method capable of decomposing into monomers in a short time under relatively mild conditions, a method of adding an alcohol and an ether to polyethylene terephthalate and generating terephthalate by reaction with an equivalent or excess amount of a base has been proposed (Patent Document 1, Non-Patent Document 1, etc.).

[0010] Prior Art Documents

[0011] Patent Documents

[0012] Patent Document 1: Japanese Patent Application Laid-Open No. 10-087529

[0013] Non-Patent Documents

[0014] Non-Patent Document 1: Oku et. al, Polymer Journal, vol. 29, No. 9, 708-712 (1997) SUMMARY

[0015] PROBLEMS TO BE SOLVED BY THE INVENTION

[0016] Patent Document 1 describes that polyethylene terephthalate is reacted with sodium hydroxide to perform depolymerization, and can be decomposed into terephthalate and ethylene glycol, and that the depolymerization reaction is performed at 40 to 75°C. However, from the viewpoint of the reaction rate of depolymerization (i.e., the conversion rate from polyethylene terephthalate to terephthalic acid), there is still room for improvement. In addition, ethers sometimes generate peroxides due to deterioration, and thus there are concerns in terms of implementing depolymerization of polyesters using ethers in industry.

[0017] The present invention relates to a method for depolymerizing a polyester in which the conversion rate to a dicarboxylic acid (e.g., terephthalic acid) or a hydroxycarboxylic acid based on depolymerization is excellent even under mild reaction conditions.

[0018] METHOD FOR SOLVING THE PROBLEM

[0019] The present inventors found that, in the case of preparing a composition containing a prescribed basic compound such as sodium hydroxide and an alcohol solvent and / or a ketone solvent and performing depolymerization of a polyester using the composition, the conversion rate to terephthalic acid is greatly affected by the amount of solvent used. The present invention is based on these insights.

[0020] The present invention includes the following. [1]

[0022] A method for depolymerizing a polyester, wherein the method includes a step of forming a mixture containing the following components (a), (b), and (c) and depolymerizing the above polyester in the mixture,

[0023] (a) a polyester;

[0024] (b) one or more basic compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, and alkaline earth metal bicarbonates; and

[0025] (c) a solvent containing at least one of an alcohol solvent or a ketone solvent,

[0026] The temperature of the mixture at the time when the mixture containing the total amount of the polyester, the basic compound, and the solvent is formed is 75°C or lower,

[0027] The ratio of the amount of the polyester to the amount of the solvent is 0.2 to 20 on a mass basis. [2]

[0029] The method according to [1], wherein the basic compound dissolves 100 g or more with respect to 100 g of water at 20 ± 5°C. [3]

[0031] The method according to [1] or [2], wherein the basic compound is one or more selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates. [4]

[0033] The method according to [1] or [2], wherein the basic compound is an alkali metal hydroxide, an alkaline earth metal hydroxide, or both. [5]

[0035] The method according to any one of [1] to [4], wherein the basic compound is one or more of an alkali metal hydroxide or an alkaline earth metal hydroxide, and the total amount of hydroxide ions in the alkali metal hydroxide and the alkaline earth metal hydroxide is in the range of 0.9 to 3.0 with respect to the amount of the repeating unit of the polyester before the mixture is formed. [6]

[0037] The method according to any one of [1] to [5], wherein the temperature of the mixture at the time when the mixture containing the total amount of the polyester, the basic compound, and the solvent is formed is 0 to 75°C. [7]

[0039] The method according to any one of [1] to [6], wherein the temperature of the mixture at the time when the mixture containing the total amount of the polyester, the basic compound, and the solvent is formed is 35 to 55°C. [8]

[0041] The method according to any one of [1] to [7], wherein the ratio of the amount of the polyester to the amount of the solvent is 0.25 to 2.2 on a mass basis. [9]

[0043] The method according to any one of [1] to [8], wherein the polyester is polyethylene terephthalate.

[10]

[0045] The method according to any one of [1] to [9], wherein the basic compound is sodium hydroxide, potassium hydroxide, or both.

[11]

[0047] The method according to any one of [1] to

[10] , wherein the alcoholic solvent is a lower alcohol.

[12]

[0049] The method according to any one of [1] to

[11] , wherein the mixture contains particles containing the polyester.

[13]

[0051] The method according to

[12] , wherein the particles containing the polyester are granules having an average particle diameter of 150 to 350 μm.

[14]

[0053] The method according to

[12] or

[13] , wherein the particles containing the polyester have a crystallinity of 50% or less.

[15]

[0055] The method according to any one of

[12] to

[14] , wherein the mixture is a powder-like mixture containing the particles containing the polyester and the solvent integrated with the particles.

[16]

[0057] The method according to any one of [1] to

[15] , wherein the polyester before the formation of the mixture has an intrinsic viscosity of 0.8 dl / g or less.

[17]

[0059] The method according to any one of [1] to

[16] , wherein the polyester is prepared from a used bottle container containing the polyester.

[18]

[0061] A method of producing a diol and a dicarboxylic acid, comprising: generating a diol and a dicarboxylic acid salt from a polyester by the method according to any one of [1] to

[17] .

[19]

[0063] A method of recycling a polyester, comprising producing a polyester by polymerization of a polymerization raw material, the polymerization raw material containing at least one of the above-mentioned diol obtained by the method according to

[18] or a dicarboxylic acid generated from the above-mentioned dicarboxylic acid salt obtained by the method according to

[18] .

[0064] [1]'

[0065] A method of depolymerizing a polyester, characterized by comprising a step of mixing components (a), (b) and (c) below,

[0066] (a) a polyester;

[0067] (b) one or more alkali metal compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates and alkaline earth metal bicarbonates;

[0068] (c) a solvent containing an alcohol solvent and / or a ketone solvent,

[0069] the above-mentioned mixing is performed at 75°C or lower,

[0070] the above-mentioned components (a), (b) and (c) are mixed in such a manner that the above-mentioned component (a) is 0.2 to 20 in mass based on the above-mentioned component (c).

[0071] [2]'

[0072] The method according to [1]', wherein the above-mentioned component (b) is an alkali metal hydroxide and / or an alkaline earth metal hydroxide, and the amount of substance of the hydroxide ion of the above-mentioned alkali metal hydroxide and / or alkaline earth metal hydroxide is in the range of 1.8 to 3.0 relative to the amount of substance of the repeating unit of the above-mentioned polyester added to the above-mentioned alcohol solvent and / or ketone solvent.

[0073] [3]'

[0074] The method according to [1] or [2]', wherein the above-mentioned mixing is performed at 35 to 55°C.

[0075] [4]'

[0076] The method according to any one of [1] to [3], wherein the above-mentioned component (a) is 0.25 to 2.2 in mass based on the above-mentioned component (c).

[0077] [5]'

[0078] The method according to any one of [1] to [4], wherein the above-mentioned (a) polyester is polyethylene terephthalate.

[0079] [6]'

[0080] The method according to any one of [1]'to [5] ', wherein the component (b) is sodium hydroxide or potassium hydroxide.

[0081] [7] '

[0082] The method according to any one of [1]'to [6] ', wherein the alcohol solvent is a lower alcohol.

[0083] [8] '

[0084] The method according to any one of [1]'to [7] ', wherein the (a) polyester is a particulate having an average particle diameter of 150 to 350 μm.

[0085] [9] '

[0086] The method according to any one of [1]'to [8] ', wherein the (a) polyester has a crystallinity of 50% or less.

[0087]

[10] '

[0088] The method according to any one of [1]'to [9] ', wherein the (a) polyester has an intrinsic viscosity of 0.8 dl / g or less.

[0089]

[11] '

[0090] The method according to any one of [1]'to

[10] ', wherein the (a) polyester is prepared from a used bottle container composed of a polyester.

[0091]

[12] '

[0092] A production method of producing a diol component and a dicarboxylic acid component by depolymerizing a polyester, which is carried out by the method according to any one of [1]'to

[11] '.

[0093]

[13] '

[0094] A recycling method of a polyester, wherein a product obtained by the method according to any one of [1]'to

[11] 'is used as at least a part of a polyester polymerization raw material to regenerate a polyester.

[0095] Effects of the Invention

[0096] According to the present invention, there is provided a method for depolymerizing a polyester, which is excellent in conversion rate to a dicarboxylic acid such as terephthalic acid or a hydroxycarboxylic acid based on depolymerization even under mild reaction conditions. The method of the present invention can be used for industrial recycling of used polyester products. DETAILED DESCRIPTION

[0097] <Method for depolymerizing polyester>

[0098] One example of the method for depolymerizing polyester includes mixing a polyester (hereinafter also referred to as "component (a)"), a prescribed basic compound (hereinafter also referred to as "component (b)") and a solvent containing an alcohol solvent and / or a ketone solvent (hereinafter also referred to as "component (c)"). The basic compound contains at least one of an alkali metal compound or an alkaline earth metal compound. The solvent contains at least one of an alcohol solvent or a ketone solvent. The step of mixing the polyester, the basic compound and the solvent includes first mixing them with each other to form a mixture, and stirring or kneading the formed mixture. The polyester is depolymerized in the formed mixture. A powder containing a particle containing the polyester can also be mixed with the basic compound and the solvent. Hereinafter, one example of the method for depolymerizing polyester based on the present application is described in detail.

[0099] The polyester is typically a polymer formed by polycondensation of one or more kinds of dicarboxylic acids and one or more kinds of diols. The basic compound of component (b) reacts with the polyester of component (a) to generate a dicarboxylic acid salt and a diol. That is, a depolymerization reaction in which the polyester is decomposed into a dicarboxylic acid salt and a diol is performed. If polyethylene terephthalate is taken as an example, terephthalic acid salt and ethylene glycol are generated. In this reaction (depolymerization reaction), by the presence of the solvent containing an alcohol solvent and / or a ketone solvent in a prescribed ratio with respect to the amount of the polyester, the depolymerization reaction is efficiently performed even under a mild condition of 75°C or lower. Specifically, in the mixture, the ratio of the amount of the polyester with respect to the amount of the solvent of component (c) can be 0.2 to 20 on a mass basis. That is, by mixing components (a), (b) and (c) in a manner that the polyester is in the range of 0.2 to 20 with respect to the alcohol solvent and / or the ketone solvent of component (c) on a mass basis, the polyester can be efficiently decomposed into a dicarboxylic acid salt and a diol even under a mild condition. The polyester can be a polymer formed by polycondensation of a hydroxycarboxylic acid compound having a hydroxyl group and a carboxyl group (for example, lactic acid). In this case, by depolymerization of the polyester under a mild condition, a salt of the hydroxycarboxylic acid compound can be formed. In the salt of the hydroxycarboxylic acid compound, generally the carboxyl group forms a salt. The polyester can contain a dicarboxylic acid unit derived from a dicarboxylic acid, a diol unit derived from a diol and a hydroxycarboxylic acid unit derived from a hydroxycarboxylic acid.

[0100] When the ratio of the amount of the polyester to the amount of the solvent (component (a) to component (c)) is less than 0.2 on a mass basis, there is a tendency that the conversion rate to a dicarboxylic acid salt or the like under mild conditions is easily reduced. On the other hand, when the ratio of the amount of the polyester to the amount of the solvent (component (a) to component (c)) is more than 20 on a mass basis, there is a tendency that the depolymerization reaction of the polyester is difficult to proceed uniformly or does not proceed because of too small amount of the solvent, and the conversion rate to a dicarboxylic acid salt or the like is easily reduced. From the same viewpoint, the ratio of the amount of the polyester to the amount of the solvent can be 0.25 or more, 0.3 or more, or 0.35 or more on a mass basis, and can be 10 or less, 5.0 or less, 3.0 or less, 2.2 or less, 2.0 or less, or 1.0 or less on a mass basis. The ratio of the amount of the polyester to the amount of the solvent can be 0.25 to 10, 0.3 to 10, 0.35 to 10, 0.25 to 5.0, 0.3 to 5.0, 0.35 to 5.0, 0.25 to 3.0, 0.3 to 3.0, 0.35 to 3.0, 0.25 to 2.2, 0.3 to 2.2, 0.35 to 2.2, 0.25 to 2.0, 0.3 to 2.0, 0.35 to 2.0, 0.25 to 1.0, 0.3 to 1.0, or 0.35 to 1.0 on a mass basis.

[0101] The basic compound (component (b)) used in the present application is not particularly limited as long as it is one or more selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, and alkaline earth metal bicarbonates.

[0102] As examples of the alkali metal hydroxides, lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, and francium hydroxide can be given. As examples of the alkali metal carbonates, lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, cesium carbonate, and francium carbonate can be given. As examples of the alkali metal bicarbonates, lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, rubidium bicarbonate, cesium bicarbonate, and francium bicarbonate can be given. As examples of the alkaline earth metal hydroxides, beryllium hydroxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, and radium hydroxide can be given. As examples of the alkaline earth metal carbonates, beryllium carbonate, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, and radium carbonate can be given. As examples of the alkaline earth metal bicarbonates, beryllium bicarbonate, magnesium bicarbonate, calcium bicarbonate, strontium bicarbonate, barium bicarbonate, and radium bicarbonate can be given.

[0103] The basic compound can be a basic compound that is easily dissolved in the solvent constituting the mixture. Both the alcoholic solvent and the ketonic solvent are solvents having a high hydrophilicity, and therefore, generally, the more a basic compound shows a higher solubility with respect to water, the more it tends to show a higher solubility in a solvent containing at least one of the alcoholic solvent or the ketonic solvent. Therefore, the magnitude of the solubility with respect to water can be used as an index to select a basic compound that is easily dissolved in a solvent containing at least one of the alcoholic solvent or the ketonic solvent. From this viewpoint, the basic compound can be a basic compound that dissolves 100 g or more with respect to 100 g of water at 20 ± 5°C. "100 g or more" herein means that the amount of the basic compound dissolved in 100 g of water at 20 ± 5°C is 100 g or more, and is sometimes written as 100 g / 100 g-H2O or more. The same applies to other numerical ranges. The amount of the basic compound dissolved in water at 20 ± 5°C can be 100 g / 100 g-H2O or more, preferably 102 g / 100 g-H2O or more, more preferably 104 g / 100 g-H2O or more, and further preferably 106 g / 100 g-H2O or more. The upper limit of the amount of the basic compound dissolved in water at 20 ± 5°C is not particularly limited, and can be, for example, 300 g / 100 g-H2O or less. Also, the amount of the basic compound dissolved in water at 20 ± 5°C can be 100 to 300 g / 100 g-H2O, preferably 102 to 300 g / 100 g-H2O, more preferably 104 to 300 g / 100 g-H2O, and further preferably 106 to 300 g / 100 g-H2O.

[0104] The basic compound can be one or more alkali metal compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates. In particular, the basic compound can be sodium hydroxide, potassium hydroxide, or both.

[0105] In one example of the present application, the amount of substance of the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide contained in the mixture together with the solvent containing an alcohol solvent and / or a ketone solvent, in other words, the total amount of substance of the hydroxide ion in the alkali metal hydroxide and the hydroxide ion in the alkaline earth metal hydroxide, can be adjusted to a range of 1.8 to 3.0 relative to the amount of substance when the repeating unit of the added polyester is the basis. The "amount of substance when the repeating unit of the polyester is the basis" is the amount expressed in moles of the total amount of the repeating unit composed of the polycarboxylic acid unit and the diol unit contained in the polyester and the total amount of the repeating unit composed of the hydroxycarboxylic acid unit contained in the polyester. By making the amount of substance of the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide 1.8 or more relative to the amount of substance when the repeating unit of the polyester is the basis, when the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide is all consumed in the depolymerization reaction, the conversion rate to the carboxylate or the salt of the hydroxycarboxylic acid easily reaches 90% or more. On the other hand, when the amount of substance of the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide is 3.0 or less relative to the amount of substance when the repeating unit of the polyester is the basis, when the generated polyester salt (dicarboxylic acid salt or salt of the hydroxycarboxylic acid) is neutralized with an acid to be converted to a free body, the chemical cost for neutralizing the excess hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide and the disposal cost of the neutralized salt are reduced, and thus it will be economically advantageous.

[0106] In another embodiment, by making the amount of substance of the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide 0.9 or more relative to the amount of substance when the repeating unit of the polyester is the basis, when the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide is all consumed in the depolymerization reaction, the conversion rate to the carboxylate or the salt of the hydroxycarboxylic acid easily reaches 90% or more. On the other hand, when the amount of substance of the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide is 1.5 or less relative to the amount of substance when the repeating unit of the polyester is the basis, when the generated polyester salt (dicarboxylic acid salt or salt of the hydroxycarboxylic acid) is neutralized with an acid to be converted to a free body, the chemical cost for neutralizing the excess hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide and the disposal cost of the neutralized salt are reduced, and thus it will be economically advantageous.

[0107] According to the above, the amount of substance of the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide with respect to the amount of substance of the repeating unit of the polyester can be 0.7 to 5.0, preferably 0.9 to 3.0, more preferably 1.8 to 3.0. In another embodiment, the amount of substance of the hydroxide ion of the alkali metal hydroxide and / or the alkaline earth metal hydroxide is preferably 0.7 to 2.0, more preferably 0.9 to 1.5.

[0108] The total amount of the basic compound can be dissolved in the solvent, or a part or all of the basic compound can be dispersed in the mixture in the form of a solid without being dissolved in the solvent. In particular, the alkali metal hydroxide and / or the alkaline earth metal hydroxide can be dissolved in the solvent containing the alcoholic solvent and / or the ketonic solvent. The alkali metal hydroxide and / or the alkaline earth metal hydroxide can also be dispersed in the form of a solid without being dissolved in the solvent.

[0109] By setting the concentrations of the above-mentioned component (a) polyester, component (c) solvent containing an alcoholic solvent and / or a ketonic solvent, and component (b) basic compound to the above-mentioned ranges, the polyester can be efficiently decomposed into a dicarboxylic acid salt and a diol or the like even under mild reaction conditions of 75°C or less. The depolymerization reaction can be performed at a temperature lower than the boiling point of the used alcoholic solvent (or ketonic solvent), for example, at 0 to 75°C, 1 to 75°C, 10 to 75°C, 15 to 75°C, 20 to 70°C, or 35 to 55°C. In other words, the temperature of the mixture at the time when the mixture containing the total amount of the polyester, the basic compound, and the solvent is initially formed can be 75°C or less, 0 to 75°C, 1 to 75°C, 10 to 75°C, 20 to 70°C, or 35 to 55°C. Even if the depolymerization reaction is performed at a temperature exceeding 75°C, the used solvent is easily volatilized in this case. Even under high-temperature conditions, if the depolymerization reaction is performed under a pressurized condition, the volatilization of the solvent can be suppressed, but if the conditions are low-temperature conditions, a complicated device for pressurization is not necessarily required, and thus it is industrially advantageous. The temperature of the mixture during stirring or kneading of the mixture after the formation of the mixture can be within the above-mentioned range. However, the temperature of the mixture can exceed 75°C due to reaction heat or the like. The temperature of the mixture during stirring or kneading of the mixture can be below the boiling point of the solvent. The mixture can also be stirred or kneaded without heating the mixture under an environment at room temperature (5 to 45°C).

[0110] The alcohol solvent used is not particularly limited, and as examples thereof, methanol, ethanol, propanol, isopropanol, butanol, and benzyl alcohol can be given. The alcohol solvent can be a lower alcohol. The lower alcohol can be an alkyl alcohol having 1 to 5 carbon atoms. The alcohol solvent can contain butanol, propanol, isopropanol, ethanol, methanol, or a combination of two or more selected from among these, and in particular, can contain ethanol, methanol, or a combination thereof. The alcohol solvent can be one kind, or two or more kinds. The alcohol solvent mixed with the polyester and the basic compound can contain a trace amount of water.

[0111] The ketone solvent used is not particularly limited, and as examples thereof, acetone, methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, isophorone, phenylethanone, and benzophenone can be given. The ketone solvent can be one kind, or two or more kinds. The ketone solvent mixed with the polyester and the basic compound can contain a trace amount of water.

[0112] In one example of the present application, the solvent contains an alcohol solvent, particularly methanol or ethanol. However, the solvent contained in the mixture together with the above-described prescribed basic compound can also contain other solvents other than the alcohol solvent and / or the ketone solvent. For example, the solvent can contain water. In this case, the ratio of the amount of the polyester to the mass of the entire solvent including other solvents other than the alcohol solvent and / or the ketone solvent can be 0.2 to 20 on a mass basis. If a solvent that can dissolve the salt of the dicarboxylic acid or the salt of the hydroxycarboxylic acid, such as water, is contained in the composition or the solvent containing the basic compound mixed with the polyester, there is a tendency that the depolymerization reaction rate becomes slow, and as a result, the conversion rate from the polyester to the salt of the dicarboxylic acid or the salt of the hydroxycarboxylic acid can relatively decrease. Therefore, in the solvent contained in the mixture together with the basic compound, the proportion of the total amount of the alcohol solvent and the ketone solvent based on the entire amount of the solvent can be 50 mass% or more, 70 mass% or more, or 90 mass% or more, or can be 100 mass% or less. In the solvent contained in the mixture together with the basic compound, the proportion of the total amount of the alcohol solvent and the ketone solvent based on the entire amount of the solvent can be 50 to 100 mass%, 70 to 100 mass%, or 90 to 100 mass%.

[0113] The polyester applicable to the depolymerization method of the present invention can be a polyester obtained by polycondensation of a diol component (diol) and a dicarboxylic acid component (dicarboxylic acid), or a polyester obtained by polycondensation of a compound having both hydroxyl and carboxyl groups in its molecule. Examples of polyesters include: aromatic polyesters such as polyethylene terephthalate, polyethylene terephthalate, polyethylene terephthalate, polyethylene naphthalate, and polyethylene furanate; fully aromatic polyesters such as polyarylates and liquid crystal polymers; polycarbonates such as polycarbonates; aliphatic polyesters such as polylactic acid polymers, polybutylene succinate polymers, polyethylene adipate polymers, polyethylene succinate polymers, polycaprolactone polymers, and polyhydroxyalkanoate polymers; and aliphatic aromatic polyesters such as polybutylene adipate, polyethylene adipate, and polyethylene terephthalate. Among these, polyethylene terephthalate (PET), which is used extensively as a bottle container material, is particularly useful.

[0114] Polyethylene terephthalate (PET) is obtained by polycondensation of ethylene glycol and terephthalic acid, which are the main monomers. In addition to these two components, PET may also contain other monomers as copolymers, either glycols or dicarboxylic acids.

[0115] Examples of dicarboxylic acid components that serve as copolymers of polyethylene terephthalate include malonic acid, succinic acid, glutaric acid, adipic acid, octanoic acid, sebacic acid, dodecanoic acid, eicosanoic acid, pimelic acid, azelaic acid, methylmalonic acid and ethylmalonic acid, adamantane dicarboxylic acid, norbornene dicarboxylic acid, cyclohexane dicarboxylic acid, naphthane dicarboxylic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, sodium isophthalate-5-sulfonate, phenylindocyanine dicarboxylic acid, anthracene dicarboxylic acid, phenanthrene dicarboxylic acid, 9,9'-bis(4-carboxyphenyl)fluorene acid, 2,5-furan dicarboxylic acid and their ester derivatives.

[0116] Examples of diols used as copolymer components of polyethylene terephthalate include 1,2-propanediol, 1,3-propanediol, butanediol, 2-methyl-1,3-propanediol, hexanediol, neopentyl glycol, cyclohexanediethanol, cyclohexanediethanol, decahydronaphthalenediethanol, decahydronaphthalenediethanol, norbornanediethanol, norbornanediethanol, tricyclodecanediethanol, tricyclodecanediethanol, tetracyclododecanediethanol, tetracyclododecanediethanol, naphthanediethanol, naphthanediethanol, 5-hydroxymethyl-5-ethyl-2-(1,1-dimethyl-2-hydroxyethyl)-1,3-di- alkane, cyclohexanediol, bicyclohexyl-4,4'-diol, 2,2-bis(4-hydroxycyclohexyl)propane, 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, cyclopentanediol, 3-methyl-1,2-cyclopentanediol, 4-cyclopenten-1,3-diol, adamantanediol, p-xylenediol, bisphenol A, bisphenol S, styrene diol, trimethylolpropane, pentaerythritol, and bis-β-hydroxyethyl terephthalate (BHET).

[0117] Polyethylene terephthalate, which is a raw material of PET bottles, is known to be a partially crystalline polymer having both amorphous and crystalline portions. The polyester can contain a copolymerization component that reduces crystallinity. For example, polyethylene terephthalate containing isophthalic acid and adipic acid and the like as copolymerization components as dicarboxylic acid components has low crystallinity, and the conversion rate to dicarboxylic acid salts at depolymerization is excellent.

[0118] The polyester to be subjected to depolymerization is not limited in crystallinity, and can be 50% or less. The crystallinity of the polyester-containing particles can be 50% or less. From the viewpoint of the conversion efficiency from the polyester to dicarboxylic acid salts or hydroxycarboxylic acids, it is advantageous that the polyester to be subjected to depolymerization has low crystallinity, but even if the polyester has a crystallinity of about 50% (crystallized polyester), the conversion to dicarboxylic acid salts or hydroxycarboxylic acids can be efficiently performed under mild conditions according to the method of the present application. The depolymerization reaction is more easily performed when the polyester has low crystallinity, and thus the conversion efficiency to dicarboxylic acid salts or hydroxycarboxylic acids can be particularly improved. The crystallinity of the polyester (the polyester-containing particles) can be 40% or less or 20% or less. As described above, the crystallinity can be adjusted by adding a comonomer to the polyester and the like.

[0119] The crystallinity refers to the crystallinity determined by wide-angle X-ray diffraction, and specifically, can be calculated from a wide-angle X-ray diffraction pattern by the following formula.

[0120] Crystallinity (%) = {integral value of crystalline peak / (integral value of crystalline peak + integral value of amorphous peak)} x 100

[0121] The intrinsic viscosity (IV) of the polyester can be 0.8 dl / g or less. When the intrinsic viscosity is low, there is a tendency that the molecular weight of the polyester is smaller, which can contribute to more efficient depolymerization. Even if the intrinsic viscosity of the polyester constituting a used polyester product (for example, a bottle container) is high, the intrinsic viscosity of a sheet or the like formed by re-melting the polyester for recycling is reduced. The lower limit of the intrinsic viscosity is not particularly limited, and about 0.3 dl / g can be the lower limit value of the intrinsic viscosity. The intrinsic viscosity of the polyester can be 0.3 to 0.8 dl / g.

[0122] The shape of the polyester can be a powder composed of polyester-containing particles. According to the Powder Technology Dictionary, the basic properties of a powder are characterized by the particle shape and particle size. The particles constituting the polyester powder can take various geometric shapes generated by various processes, such as cubical, granular, blocky, platy, flaky, membranous (a flaky thin powder particle, thinner than flaky), prismoidal, rodlike, acicular, needle-like, fibrous, dendritic, sponge, angular, sharp-edged, sharp-cornered, modular, rounded, irregular, or crystalline. The shape of the particles is based on the mechanical properties and crystallographic properties of the substance constituting the particles, and also depends on the generation process (http: / / www.sptj.jp / powderpedia / words / 12474 / ). In the present application, the polyester-containing particles can have any shape including the above-mentioned shapes. The polyester-containing particles can be flaky, fibrous, membranous, or granular, can be flaky or granular, or can be granular. That is, the mixture can include polyester-containing granular substances.

[0123] The average particle size of the polyester-containing granular substance is not particularly limited, and can be 150 to 350 μm or 200 to 300 μm. Here, the average particle size refers to the 50% particle size (D50: median particle size) in the cumulative distribution of the particle size distribution measured by the laser diffraction scattering method. The maximum particle size of the polyester-containing granular substance can be 200 to 1000 μm, 250 to 500 μm, or 250 to 400 μm.

[0124] The longest side of the polyester-containing flaky particles can be, for example, 1 to 50 mm, 1 to 20 mm, or 5 to 15 mm. The substance recovered from used PET bottles and small-particleized is generally mostly in a flaky shape, but the flaky particles are not limited to the substance recovered from used PET bottles.

[0125] The longest side of the polyester-containing fibrous particles (the length of the fibrous particles) can be 1 to 500 mm or 1 to 200 mm. The fibrous particles can be short fibers having a longest side (length) of about 1 mm to about 100 mm. The fibrous polyester can be a PET fiber used in clothing, but the fibrous polyester is not limited thereto.

[0126] The longest side of the film-like particles containing polyester can be, for example, about 1 mm to about 200 mm, about 1 mm to about 100 mm, or about 1 mm to about 50 mm.

[0127] In the present application, the components (a), (b), and (c) are mixed in a manner such that the mixing ratio of each component is within the range described above. In other words, a mixture is formed by mixing the components (a), (b), and (c) in a manner such that the mixing ratio of each component is within the range described above, and the mixture is stirred or kneaded. The mixture can be a dispersion liquid containing a solution containing a basic compound and a solvent, and particles containing polyester dispersed in the solution. Alternatively, the mixture can be a powder-like mixture containing particles containing polyester and a solvent integrated with the particles. The powder-like mixture can contain a solid basic compound. The solid basic compound can be integrated with the particles containing polyester, or can form particles different from the particles containing polyester. The solvent and / or the basic compound integrated with the particles containing polyester can be attached to the surface of the particles containing polyester, or can penetrate into the inside of the particles containing polyester. In the powder-like mixture, depolymerization of the polyester can be performed particularly efficiently.

[0128] According to one example of the present application, even if the components are mixed under mild conditions at 75°C or lower, depolymerization of the polyester proceeds. From the viewpoint of the conversion rate to a salt of a dicarboxylic acid or a hydroxycarboxylic acid, mixing (stirring or kneading) can be performed for about 50 minutes or about 30 minutes. Thereby, the conversion rate to a salt of a dicarboxylic acid or a hydroxycarboxylic acid easily reaches 50% or more. Mixing refers to an operation of stirring or kneading in a container in a manner such that the composition containing a basic compound (composition containing a basic compound and a solvent) and the polyester become a uniform state. Specifically, mixing refers to stirring or kneading of a mixture containing these components. The speed of stirring and kneading is not limited. From the viewpoint of safety in work and equipment capacity, the speed of stirring (for example, the rotation speed of a stirring blade) can be, for example, 250 to 1500 rpm, 500 to 1000 rpm. The speed of kneading (for example, the rotation speed of a kneading blade) can be, for example, 5 to 150 rpm or 10 to 100 rpm.

[0129] <Method for recycling polyester>

[0130] In another example of the present application, there is provided a recycling method for recycling a polyester using a product produced by the depolymerization method of the polyester described above as at least a part of a polyester polymerization raw material. That is, by applying the depolymerization method of the polyester, a dicarboxylic acid salt and a diol are obtained as products from a polyester prepared from a used polyester product (for example, a used bottle container containing a polyester). The dicarboxylic acid salt can be isolated in the form of a solid substance. The dicarboxylic acid salt is generally used as a polyester polymerization raw material after being converted into a dicarboxylic acid. The diol can be isolated from a mixture with an alcohol solvent and / or a ketone solvent by a known operation such as fractionation. A product containing a salt of a hydroxycarboxylic acid is obtained from a polyester containing a hydroxycarboxylic acid unit. The salt of the hydroxycarboxylic acid is generally used as a polyester polymerization raw material after being converted into a hydroxycarboxylic acid.

[0131] In one example of the present application, polyethylene terephthalate is used, methanol is used as the solvent containing an alcohol solvent and / or a ketone solvent, and sodium hydroxide is used as the alkali metal hydroxide. In this case, sodium terephthalate is obtained in the form of a solid component by the depolymerization of polyethylene terephthalate, and ethylene glycol can be obtained by a fractionation operation of a mixture of ethylene glycol and methanol. The obtained sodium terephthalate can be made into terephthalic acid by adding an acid. Polyethylene terephthalate can be recycled from the terephthalic acid and ethylene glycol thus obtained. The sodium terephthalate obtained after the depolymerization can also be dissolved with water together with the mixture of ethylene glycol and methanol to make an aqueous solution containing sodium terephthalate, ethylene glycol, and methanol, and then terephthalic acid can be crystallized by adding an acid and recovered. At this time, methanol and ethylene glycol remaining in the aqueous solution can be recovered by a fractionation operation, respectively. Polyethylene terephthalate can be recycled or produced from the terephthalic acid and ethylene glycol thus obtained. As a part of the diol component and the dicarboxylic acid component used in the production of a polyester, the terephthalic acid and ethylene glycol obtained by the method of the present application can be used.

[0132] Example

[0133] Next, the present application is described in more detail by citing examples. However, the present application is not limited to these examples.

[0134] Preparation of a sample

[0135] (1) Polyester

[0136] • PET sample 1

[0137] A commercially available amorphous PET resin (PBK-1, intrinsic viscosity: 0.65 dl / g, manufactured by Bell Polyester Products Co.) was prepared. By freezing and pulverizing the PET resin, a PET sample 1 containing polyethylene terephthalate in the form of a granular substance was obtained.

[0138] The particle size distribution of the PET sample 1 was measured by a wet method using a laser diffraction type particle size distribution measuring device (ANTON PAAR, PSA 1190) using a scattering method. From the obtained particle size distribution, the 50% particle size (D50 median particle size) was calculated when expressed in a cumulative distribution, and this value was taken as the average particle size. The average particle size of the PET sample 1 was 218 μm.

[0139] Wide-angle X-ray diffraction measurement of the PET sample 1 was performed using a wide-angle X-ray diffraction device (RINT 2500HL, Rigaku Corporation). The conditions of the wide-angle X-ray diffraction measurement were as follows: the X-ray source was Cu kα ray (λ = 0.1542 nm), the output was 50 kV-250 mA, the scanning speed was 0.5 deg / minute, and the slit width DS was 0.6 mm + 10 mm H. The range of 2θ = 1.5-70° of the obtained diffraction pattern was subjected to peak fitting, and the integral intensity of the angular peak was summed up as the crystalline component and the amorphous component, respectively, and their values were taken as the crystalline component integral intensity I and the amorphous component integral intensity la. The crystallinity X was calculated from I and la according to the following formula.

[0140] X = {I / (I + la)} x 100 (%)

[0141] X: Crystallinity

[0142] I: Crystalline component integral intensity

[0143] la: Amorphous component integral intensity

[0144] The crystallinity of the PET sample 1 calculated as described above was 0.40%.

[0145] • PET sample 2

[0146] A commercially available crystalline PET resin (TK-3, intrinsic viscosity: 0.65 dl / g, manufactured by Bell Polyester Products Co.) was prepared. By freezing and pulverizing this PET resin, a PET sample 2 containing polyethylene terephthalate in the form of particles was obtained.

[0147] The average particle size of the PET sample 2 was calculated in the same manner as described above, and the result was 268 μm. The crystallinity of the PET sample 2 was calculated in the same manner as described above, and the result was 22.8%.

[0148] [Examples 1-2, Comparative Examples 1-2]

[0149] A solution was prepared by dissolving potassium hydroxide in ethanol. After adjusting the temperature of the solution to 40°C, PET sample 1 was added to the solution, thereby forming a mixture as a dispersion liquid containing PET sample 1, potassium hydroxide and ethanol in the amounts shown in Table 1. After forming the mixture, the mixture was stirred for 10 minutes at 760 rpm using a mechanical stirrer (BL600, manufactured by Shinsei Science Co., Ltd.) without heating. The mixture was stirred under four conditions in which the amount of PET sample 1 added was 5 g (26 mmol) to 30 g (156 mmol) as shown in Table 1. Under the four conditions, the amount of substance of potassium hydroxide in the solution was adjusted so as to be 2.2 with respect to the amount of substance of the repeating unit of PET. The depolymerization rate and terephthalic acid conversion rate calculated as described below are shown in Table 1. As is apparent from Table 1, the more the amount of PET sample 1 added with respect to the reaction solvent increases on a mass basis, the higher the depolymerization efficiency becomes, and a higher effect is exhibited. The "molar number of repeating units" in the table refers to the amount of substance of the repeating unit (C 10 H8O4) composed of terephthalic acid units and ethylene glycol units contained in the PET sample. The initial temperature in the table is the temperature of the mixture at the time when the total amount of PET sample was added to the solution, that is, at the time when the mixture containing the total amount of the solution and PET sample was formed.

[0150] <Depolymerization rate>

[0151] After 10 minutes from the start of stirring the mixture, a sufficient amount of water was added to the mixture (reaction liquid) to dissolve the product. The unreacted PET sample 1 was recovered by centrifugal separation. The recovered unreacted PET sample 1 was dried by heating in an oven at 100°C for 12 hours or more, and the mass W fin .

[0152] The depolymerization rate was calculated using the following calculation formula.

[0153] Depolymerization rate (%) = [(W int -W fin ) / W int ] x 100

[0154] In the above formula, W int represents the mass (g) of PET sample 1 supplied to the reaction, and W fin represents the mass (g) of unreacted PET sample 1 recovered after the reaction.

[0155] <Terephthalic acid conversion rate>

[0156] The centrifugal supernatant at the time of centrifugal separation for recovering the unreacted PET sample 1 was put into a volumetric flask, and water was added thereto so as to make the total amount 1 L. A part of the solution in the volumetric flask was diluted to 100 times using a diluent (1 N aqueous HC1: isopropyl alcohol = 1 : 9 (v / v)). The diluted solution was used as a sample, and terephthalic acid was quantified by HPLC. The conditions of HPLC measurement were as described below.

[0157] Column: L-column 2 ODS 2.1 mm x 150 mm, particle size 2 μm (Chemical Evaluation and Research Institute)

[0158] Column temperature: 35°C

[0159] Mobile phase A: water containing 0.1% acetic acid

[0160] Mobile phase B: acetonitrile containing 0.1% acetic acid

[0161] Flow rate: 0.2 mL / min

[0162] Linear gradient: 15% B (0 min) → 80% B (26 min)

[0163] Detector: photodiode array (wavelength 190 to 600 nm)

[0164] Based on the quantitative results by HPLC, the conversion rate of terephthalic acid was calculated according to the following equation.

[0165] Conversion rate (%) = [(W tpa / 166) / (W int / 192)] x 100

[0166] In the above equation, W int is the mass (g) of the PET sample 1 supplied to the reaction, W tpa is the amount (g) of terephthalic acid calculated based on the quantitative results by HPLC, 166 is the molecular weight of terephthalic acid, and 192 is the formula weight of the repeating unit (C 10 H8O4) of PET.

[0167]

[0168] [Examples 3 to 4, Comparative Examples 3 to 4]

[0169] After adjusting the temperature of a solution in which potassium hydroxide was added to ethanol to 50°C, PET sample 2 was added to the solution, thereby forming a mixture as a dispersion liquid containing the PET sample 2, potassium hydroxide and ethanol in the amounts shown in Table 2. The mixture formed was stirred, and the experiment was conducted in the same manner as in Examples 1 to 2 and Comparative Examples 1 to 2, except for this, and the depolymerization rate and terephthalic acid conversion rate were calculated. The results obtained are shown in Table 2. As is apparent from Table 2, the more the amount of PET sample 2 added with respect to the reaction solvent in mass basis increases, the more the depolymerization efficiency increases, and a higher effect is exhibited.

[0170]

[0171] [Example 5]

[0172] A solution was prepared by dissolving sodium hydroxide in methanol. After adjusting the temperature of the solution to 40°C, 30 g of PET sample 1 was added to the solution, thereby forming a mixture as a dispersion liquid containing the PET sample 1, sodium hydroxide and methanol in the amounts shown in Table 3. The mixture formed was stirred, and the experiment was conducted in the same manner as in Example 1, except for this, and the depolymerization rate and terephthalic acid conversion rate were calculated. The results obtained are shown in Table 3. For comparison, Example 1 is also shown in Table 3.

[0173]

[0174] [Example 6]

[0175] After adjusting the temperature of a solution in which sodium hydroxide was added to a mixed solvent of methanol / water (methanol: water (mass basis) = about 7:3) to 40°C, PET sample 1 was added to the solution, thereby forming a mixture as a dispersion liquid containing the PET sample 1, sodium hydroxide and the mixed solvent (methanol / water) in the amounts shown in Table 4. The mixture formed was stirred, and the experiment was conducted in the same manner as in Example 1, except for this, and the depolymerization rate and terephthalic acid conversion rate were calculated. The results obtained are shown in Table 4.

[0176] [Example 7]

[0177] After adjusting the temperature of a solution in which sodium hydroxide was added to a mixed solvent of methanol / water (methanol: water (mass basis) = about 7:3) to 50°C, PET sample 2 was added to the solution, thereby forming a mixture as a dispersion liquid containing the PET sample 2, sodium hydroxide and the mixed solvent (methanol / water) in the amounts shown in Table 4. The mixture formed was stirred, and the experiment was conducted in the same manner as in Example 3, except for this, and the depolymerization rate and terephthalic acid conversion rate were calculated. The results obtained are shown in Table 4.

[0178] [Comparative Example 5]

[0179] After adjusting the temperature of the solution in which sodium hydroxide was added to water to 40°C, PET sample 1 was added to the solution, thereby forming a mixture as a dispersion liquid containing PET sample 1, sodium hydroxide, and water in the amounts shown in Table 4. The formed mixture was stirred, and the experiment was conducted in the same manner as in Example 6 except for this, and the depolymerization rate and terephthalic acid conversion rate were calculated. The results obtained are shown in Table 4.

[0180] As is also apparent from Table 4, under the conditions of Examples 6 and 7 in which a mixed solvent containing methanol and water in a ratio of about 7:3 on a mass basis was used, a high depolymerization rate of 70% or more was shown. In contrast, in Comparative Example 5 in which only water was used as the solvent, although the PET addition amount was as high as a value of 0.613 on a mass basis with respect to the reaction solvent, the depolymerization rate was as low as a value of less than 3%. This result suggests that the solvent containing an alcoholic solvent is more advantageous in terms of improving the depolymerization efficiency.

[0181]

[0182] [Example 8]

[0183] As PET sample 3, a commercially available crystalline PET resin powder (granular material, ES30-PD-000132, intrinsic viscosity: 0.80 dl / g, maximum particle diameter: 300 μm, manufactured by Goodfellow) was prepared. The crystallinity of PET sample 3 was calculated in the same manner as in PET sample 1, and the result was 39.5%.

[0184] Methanol 150 g was heated to 50°C in a kneader (HIVIS DISPER MIX 3D-2 type, manufactured by PRIMIX Corporation). To this, sodium hydroxide 137 g (3.43 mol) and 300 g (amount of substance on the basis of repeating units: 1.56 mol) of PET sample 3 were added, thereby forming a powder-like mixture containing PET sample 3, sodium hydroxide, and methanol in the amounts shown in Table 5. The formed powder-like mixture was kneaded at a rotation speed of 40 rpm for 15 minutes without heating. The depolymerization rate and terephthalic acid conversion rate are shown in Table 5.

[0185]

[0186] [Example 9]

[0187] PET sample 4 was prepared by thinning a recycled PET bottle. PET sample 4 was a powder containing a particle having a thin sheet shape with a size of 0.5 to 1 cm. The crystallinity of a sample obtained by freezing and pulverizing PET sample 4 was measured in the same manner as in PET sample 1, and the result was 8.8%.

[0188] A flaky PET sample 4 was directly supplied to the depolymerization test. Methanol 150 g was put into a table kneader (PNV-1, Kabushiki Kaisha Iriki Shoten) and heated to 50°C. To this, sodium hydroxide 137 g (3.43 mol) and 300 g (amount of substance on the basis of repeating units: 1.56 mol) of the PET sample 4 were added, thereby forming a powder-like mixture containing the PET sample 4, sodium hydroxide, and methanol in the amounts shown in Table 6. The formed powder-like mixture was kneaded at a rotation speed of 40 rpm for 30 minutes without heating. The depolymerization rate and the terephthalic acid conversion rate are shown in Table 6.

[0189]

[0190] [Example 10]

[0191] Methanol 155 g was put into a table kneader (PNV-1, Kabushiki Kaisha Iriki Shoten) and heated to 50°C. To this, sodium hydroxide 114 g (2.85 mol) and 250 g (amount of substance on the basis of repeating units: 1.30 mol) of the PET sample 3 were added, thereby forming a powder-like mixture containing the PET sample 4, sodium hydroxide, and methanol in the amounts shown in Table 7. The formed powder-like mixture was kneaded at a rotation speed of 50 rpm for 30 minutes without heating. The depolymerization rate and the terephthalic acid conversion rate are shown in Table 7.

[0192] [Example 11]

[0193] Methanol 155 g was put into a table kneader (PNV-1, Kabushiki Kaisha Iriki Shoten). To the methanol at room temperature (21°C) in the kneader, sodium hydroxide 114 g (2.85 mol) and 250 g (amount of substance on the basis of repeating units: 1.30 mol) of the PET sample 3 were added, thereby forming a powder-like mixture containing the PET sample 4, sodium hydroxide, and methanol in the amounts shown in Table 7. The formed powder-like mixture was kneaded at a rotation speed of 50 rpm for 30 minutes without heating. The depolymerization rate and the terephthalic acid conversion rate are shown in Table 7.

[0194] [Example 12]

[0195] Methanol 125 g was put into a table kneader (PNV-1, Kabushiki Kaisha Iriki Shoten). To the methanol at room temperature (21°C) in the kneader, sodium hydroxide 114 g (2.85 mol) and 250 g (amount of substance on the basis of repeating units: 1.30 mol) of the PET sample 3 were added, thereby forming a powder-like mixture containing the PET sample 4, sodium hydroxide, and methanol in the amounts shown in Table 7. The formed powder-like mixture was kneaded at a rotation speed of 50 rpm for 30 minutes without heating. The depolymerization rate and the terephthalic acid conversion rate are shown in Table 7.

[0196] [Example 13]

[0197] 125g of ethanol was placed in a benchtop kneader (PNV-1, Irie Shokai Co., Ltd.). 114g (2.85mol) of sodium hydroxide and 250g (1.30mol of PET sample 3 based on repeating units) of ethanol at room temperature (15°C) were added to the kneader, thus forming a powdery mixture containing PET sample 3, sodium hydroxide, and ethanol in the amounts shown in Table 7. The resulting powdery mixture was kneaded at 50 rpm for 8 minutes without heating. The depolymerization rate and terephthalic acid conversion rate are shown in Table 7.

[0198]

Claims

1. A method for depolymerizing polyester, wherein, The method includes the steps of forming a mixture comprising the following components (a), (b), and (c) and depolymerizing the polyester in the mixture. (a) Polyester; (b) One or more basic compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, and alkaline earth metal bicarbonates; and (c) A solvent containing at least one of an alcohol solvent or a ketone solvent. The temperature of the mixture at the moment when the total amount of the polyester, the alkaline compound, and the solvent is formed is below 75°C. The ratio of the amount of polyester to the amount of solvent is 0.2 to 20 by mass.

2. The method according to claim 1, wherein, The alkaline compound dissolves in more than 100g of water at 20±5℃.

3. The method according to claim 1, wherein, The alkaline compound is selected from one or more of the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates.

4. The method according to claim 1, wherein, The alkaline compound is an alkali metal hydroxide, an alkaline earth metal hydroxide, or both.

5. The method according to claim 1, wherein, The alkaline compound is an alkali metal hydroxide, an alkaline earth metal hydroxide, or both, wherein the total amount of hydroxide ions in the alkali metal hydroxide and the alkaline earth metal hydroxide is in the range of 0.9 to 3.0 relative to the amount of repeating unit of the polyester prior to the formation of the mixture.

6. The method according to claim 1, wherein, The temperature of the mixture at the moment when the total amount of the polyester, the alkaline compound, and the solvent is formed is 0–75°C.

7. The method according to claim 1, wherein, The temperature of the mixture at the moment when the total amount of the polyester, the alkaline compound, and the solvent is formed is 35–55°C.

8. The method according to claim 1, wherein, The ratio of the amount of polyester to the amount of solvent is 0.25 to 2.2 by mass.

9. The method according to claim 1, wherein, The polyester is polyethylene terephthalate.

10. The method according to claim 1, wherein, The alkaline compound is sodium hydroxide, potassium hydroxide, or both.

11. The method according to claim 1, wherein, The alcohol solvent is a lower alcohol.

12. The method according to claim 1, wherein, The mixture contains particles containing the polyester.

13. The method according to claim 12, wherein, The particles containing the polyester are granules with an average particle size of 150 to 350 μm.

14. The method according to claim 12, wherein, The crystallinity of the particles containing the polyester is less than 50%.

15. The method according to claim 12, wherein, The mixture is a powder mixture comprising particles containing the polyester and a solvent integrated with the particles.

16. The method according to claim 1, wherein, The polyester prior to the formation of the mixture has an intrinsic viscosity of less than 0.8 dl / g.

17. The method according to claim 1, wherein, The polyester is prepared from used bottles and containers containing polyester.

18. A method for producing diols and dicarboxylic acids, comprising: Diols and dicarboxylates are generated from polyester by the method described in any one of claims 1 to 17.

19. A method for recycling polyester, comprising generating polyester by polymerization of a polymerizing feedstock, said polymerizing feedstock comprising at least one of the diol obtained by the method of claim 18 or a dicarboxylic acid generated from the dicarboxylic acid salt obtained by the method of claim 18.

Citation Information

Patent Citations

  • Recovery of terephthalic acid and ethylene glycol from polyethylene terephthalate

    JP1998087529A

Cited By

  • A method for depolymerizing waste polyester, a recycling method, and application of alcohol

    CN122464775A